Method for preparing battery-grade nano iron phosphate through air oxidation

Through the air oxidation preparation method, the problems of uneven particles and large particle size of lithium iron phosphate battery materials were solved, and high-purity and uniform particle size nano iron phosphate were prepared, which improved the electrochemical performance and production efficiency of the battery and reduced the cost.

CN119263237APending Publication Date: 2025-01-07HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411374442.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing lithium iron phosphate battery materials have problems such as uneven particle size, large particle size and small specific surface area, resulting in low battery volume and poor electrochemical performance.

Method used

By using the air oxidation preparation method, the iron powder is dissolved in dilute phosphoric acid and heated and dispersed ultrasonically, the surfactant and deionized water are added, and the pH is adjusted for the oxidation and precipitation reaction is obtained to obtain battery-grade nano iron phosphate. The method includes the control of the molar ratio of pre-sieve iron powder to dilute phosphoric acid, dissolution temperature, ultrasonic dispersion conditions, stirring heating temperature and oxidation and precipitation reaction time.

Benefits of technology

It achieves high purity, uniform particle size distribution and regular morphology of nano iron phosphate, meets the industry standards of battery-grade materials, improves the electrochemical performance and production efficiency of the battery, and reduces costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of lithium battery materials. More specifically, the invention relates to a method for preparing battery-grade nano iron phosphate through air oxidation. According to the method for preparing the battery-grade nano iron phosphate through air oxidation, under the condition of stirring, heating and ultrasonic dispersion at the same time, iron powder is rapidly dissolved in dilute phosphoric acid, and compared with a traditional iron dissolving process, the method is higher in dissolving efficiency; the surfactant is added into the filtrate, so that the generation of large particles can be inhibited in the growth stage of iron phosphate crystal grains, then the crystal grains are controlled to uniformly and stably grow, and meanwhile, particle aggregation is reduced; deionized water is used for replacing a precipitator, so that impurities can be avoided, and the high purity of iron phosphate is ensured; air is used for replacing hydrogen peroxide, so that the production cost is remarkably reduced, the problems of incomplete reaction, substandard iron-phosphorus ratio and the like caused by the fact that the hydrogen peroxide is easily decomposed after being heated are solved, the reaction can be more sufficient, the aging step is omitted, and crystalline-state iron phosphate dihydrate is prepared in one step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery materials, and more specifically to a method for preparing battery-grade nano iron phosphate by air oxidation. Background Art

[0002] Lithium iron phosphate is an important cathode material for lithium-ion batteries, with advantages such as high structural stability, good safety performance, moderate operating voltage, good platform characteristics, and large theoretical capacity. However, lithium iron phosphate currently has problems such as uneven particles, large particle size, and small specific surface area. This results in low volume-to-capacity and poor electrochemical performance of the manufactured battery. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a method for preparing battery-grade nano-iron phosphate by air oxidation.

[0004] In order to achieve these purposes and other advantages according to the present invention, a method for preparing battery-grade nano iron phosphate by air oxidation is provided, comprising the following steps:

[0005] S1. Dissolving iron powder in dilute phosphoric acid, stirring and heating the dilute phosphoric acid during the dissolution process, ultrasonically dispersing the dilute phosphoric acid, and filtering to obtain a filtrate;

[0006] S2, adding a surfactant to the filtrate obtained in S1 to obtain a raw material solution;

[0007] S3, adding deionized water to the raw material solution obtained in S2 to adjust the pH value to 1-2, and then introducing gas under stirring and heating conditions to perform an oxidation precipitation reaction to obtain a precursor slurry;

[0008] S4. Post-process the precursor slurry obtained in S3 to obtain battery-grade nano iron phosphate.

[0009] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the iron powder in S1 is pre-sieved with a 200-mesh sieve, and the iron powder is any one or a combination of several of ductile iron with an iron content ≥97%, reduced iron powder with an iron content ≥98%, and electrolytic iron powder with an iron content ≥99%.

[0010] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the molar ratio of iron powder to phosphoric acid in S1 is 1:2-4, the mass percentage concentration of dilute phosphoric acid is 15-40%, the dissolution temperature is 20-80°C, the dissolution time is 1-2h, the ultrasonic power of ultrasonic dispersion is 100-150w, and the ultrasonic frequency is 20-30kHz.

[0011] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, when a surfactant is added to S2, the filtrate is stirred and heated.

[0012] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the filtrate is stirred and heated at a stirring speed of 400-600 rpm and a heating temperature of 50-80°C in S2.

[0013] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the surfactant in S2 is any one of citric acid, polyethylene glycol, hexadecyltrimethylammonium bromide and sodium hexadecylbenzenesulfonate.

[0014] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the mass of the surfactant added in S2 is 1-5% of the theoretical amount of the precursor slurry generated in S3.

[0015] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the flow rate of the gas introduced into S3 is 2.5-3.5 L / min, the temperature of the oxidation precipitation reaction is 80-100°C, the reaction time is 1-2h, and the stirring speed is 400-600rpm.

[0016] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the gas introduced into S3 is any one or a combination of air, oxygen and ozone.

[0017] Furthermore, in the method for preparing battery-grade nano-iron phosphate by air oxidation, the post-treatment of the precursor slurry in S4 mainly includes:

[0018] The precursor slurry obtained in S3 is filtered and washed, and calcined at a temperature of 450-550° C. for 4-6 hours to obtain nano iron phosphate.

[0019] The beneficial effects of the present invention are:

[0020] 1. In the method for preparing battery-grade nano-iron phosphate by air oxidation of the present invention, the iron powder is rapidly dissolved in dilute phosphoric acid under the conditions of stirring, heating and ultrasonic dispersion. Compared with the traditional iron dissolving process, this method has higher dissolution efficiency;

[0021] 2. In the method for preparing battery-grade nano-iron phosphate by air oxidation of the present invention, a surfactant is added to the filtrate, which can inhibit the formation of large particles in the iron phosphate grain growth stage, and then control the uniform and stable growth of the grains, while reducing particle agglomeration;

[0022] 3. In the method for preparing battery-grade nano-iron phosphate by air oxidation of the present invention, deionized water is used instead of the precipitant, which can avoid the generation of impurities and ensure the high purity of the iron phosphate;

[0023] 4. In the method for preparing battery-grade nano-iron phosphate by air oxidation of the present invention, air is used instead of hydrogen peroxide, which significantly reduces the production cost. It not only makes up for the problems of incomplete reaction and substandard iron-phosphorus ratio caused by the easy decomposition of hydrogen peroxide when heated, but also makes the reaction more complete, thereby eliminating the aging step and obtaining crystalline iron phosphate dihydrate in one step.

[0024] 5. The nano-iron phosphate prepared by the method for preparing battery-grade nano-iron phosphate by air oxidation of the present invention has high purity, uniform particle size distribution, regular morphology, and all parameters meet the industry standards for battery-grade materials.

[0025] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0027] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0028] <Example 1>

[0029] A method for preparing battery-grade nano iron phosphate by air oxidation comprises the following steps:

[0030] S1. dissolving iron powder in dilute phosphoric acid, stirring and heating the dilute phosphoric acid during the dissolution process, ultrasonically dispersing the dilute phosphoric acid, and filtering to obtain a filtrate;

[0031] S2, adding a surfactant to the filtrate obtained in S1 to obtain a raw material solution;

[0032] S3, adding deionized water to the raw material solution obtained in S2 to adjust the pH value to 2, and then introducing gas under stirring and heating conditions to carry out oxidation precipitation reaction, and the final solution pH is 1.0 to obtain a precursor slurry;

[0033] S4. Post-process the precursor slurry obtained in S3 to obtain battery-grade nano iron phosphate.

[0034] The iron powder in S1 was pre-sieved with a 200-mesh sieve.

[0035] Among them, the molar ratio of iron powder to phosphoric acid in S1 is 1:3, the mass percentage concentration of dilute phosphoric acid is 15%, the dissolution temperature is 60°C, the stirring speed is 400rpm, the dissolution time is 90min, the ultrasonic power of ultrasonic dispersion is 100w, and the ultrasonic frequency is 20kHz.

[0036] When a surfactant is added to S2, the filtrate is stirred and heated.

[0037] In S2, the filtrate is stirred and heated at a stirring speed of 400 rpm and a heating temperature of 80°C.

[0038] Wherein, the surfactant in S2 is hexadecyltrimethylammonium bromide.

[0039] The mass of the surfactant added in S2 is 1% of the iron powder added in S1.

[0040] The flow rate of the gas introduced into S3 is 2.5 L / min, the temperature of the oxidation precipitation reaction is 80° C., the reaction time is 80 min, and the stirring speed is 400 rpm.

[0041] The gas introduced into S3 is air.

[0042] Among them, the post-processing of the precursor slurry in S4 mainly includes:

[0043] The precursor slurry obtained in S3 is fully washed, placed in a forced air drying oven, and dried at 80° C. for 12 h to obtain dihydrated iron phosphate; the dihydrated iron phosphate is calcined at 550° C. for 4 h for dehydration to finally obtain nano iron phosphate.

[0044] <Example 2>

[0045] A method for preparing battery-grade nano iron phosphate by air oxidation comprises the following steps:

[0046] S1. dissolving iron powder in dilute phosphoric acid, stirring and heating the dilute phosphoric acid during the dissolution process, ultrasonically dispersing the dilute phosphoric acid, and filtering to obtain a filtrate;

[0047] S2, adding a surfactant to the filtrate obtained in S1 to obtain a raw material solution;

[0048] S3, adding deionized water to the raw material solution obtained in S2 to adjust the pH value to 2, and then introducing gas under stirring and heating conditions to carry out oxidation precipitation reaction, and the final solution pH is 1.0 to obtain a precursor slurry;

[0049] S4. Post-process the precursor slurry obtained in S3 to obtain battery-grade nano iron phosphate.

[0050] The iron powder in S1 was pre-sieved with a 200-mesh sieve.

[0051] Among them, the molar ratio of iron powder to phosphoric acid in S1 is 1:2.5, the mass percentage concentration of dilute phosphoric acid is 20%, the dissolution temperature is 50°C, the stirring speed is 400rpm, the dissolution time is 60min, the ultrasonic power of ultrasonic dispersion is 100w, and the ultrasonic frequency is 25kHz.

[0052] When a surfactant is added to S2, the filtrate is stirred and heated.

[0053] In S2, the filtrate is stirred and heated at a stirring speed of 400 rpm and a heating temperature of 90°C.

[0054] Wherein, the surfactant in S2 is hexadecyltrimethylammonium bromide.

[0055] The mass of the surfactant added in S2 is 1% of the iron powder added in S1.

[0056] The flow rate of the gas introduced into S3 is 3 L / min, the temperature of the oxidation precipitation reaction is 90° C., the reaction time is 100 min, and the stirring speed is 400 rpm.

[0057] The gas introduced into S3 is air.

[0058] Among them, the post-processing of the precursor slurry in S4 mainly includes:

[0059] The precursor slurry obtained in S3 is fully washed, placed in a forced air drying oven, and dried at 80° C. for 12 h to obtain dihydrated iron phosphate; the dihydrated iron phosphate is calcined at 500° C. for 3 h for dehydration to finally obtain nano iron phosphate.

[0060] <Example 3>

[0061] A method for preparing battery-grade nano iron phosphate by air oxidation comprises the following steps:

[0062] S1. dissolving iron powder in dilute phosphoric acid, stirring and heating the dilute phosphoric acid during the dissolution process, ultrasonically dispersing the dilute phosphoric acid, and filtering to obtain a filtrate;

[0063] S2, adding a surfactant to the filtrate obtained in S1 to obtain a raw material solution;

[0064] S3, adding deionized water to the raw material solution obtained in S2 to adjust the pH value to 2, and then introducing gas under stirring and heating conditions to carry out oxidation precipitation reaction, and the final solution pH is 1.0 to obtain a precursor slurry;

[0065] S4. Post-process the precursor slurry obtained in S3 to obtain battery-grade nano iron phosphate.

[0066] The iron powder in S1 was pre-sieved with a 200-mesh sieve.

[0067] The molar ratio of iron powder to phosphoric acid in S1 is 1:2, the mass percentage concentration of dilute phosphoric acid is 25%, the dissolution temperature is 60° C., the stirring speed is 400 rpm, the dissolution time is 30 min, the ultrasonic power of ultrasonic dispersion is 100 W, and the ultrasonic frequency is 30 kHz.

[0068] When a surfactant is added to S2, the filtrate is stirred and heated.

[0069] In S2, the filtrate is stirred and heated at a stirring speed of 400 rpm and a heating temperature of 100°C.

[0070] Wherein, the surfactant in S2 is hexadecyltrimethylammonium bromide.

[0071] The mass of the surfactant added in S2 is 1% of the iron powder added in S1.

[0072] The flow rate of the gas introduced into S3 is 3.5 L / min, the temperature of the oxidation precipitation reaction is 100° C., the reaction time is 120 min, and the stirring speed is 400 rpm.

[0073] Among them, the gas introduced into S3 is air.

[0074] Among them, the post-processing of the precursor slurry in S4 mainly includes:

[0075] The precursor slurry obtained in S3 is fully washed, placed in a forced air drying oven, and dried at 80° C. for 12 h to obtain dihydrated iron phosphate; the dihydrated iron phosphate is calcined at 450° C. for 2 h for dehydration to finally obtain nano iron phosphate.

[0076] <Comparative Example 1>

[0077] A method for preparing battery-grade nano-iron phosphate by air oxidation, compared with the method for preparing battery-grade nano-iron phosphate by air oxidation in Example 1, the only difference is that in S2, no surfactant is added to the filtrate obtained in S1, and the other steps and parameters are the same.

[0078] <Comparative Example 2>

[0079] A method for preparing battery-grade nano-iron phosphate by air oxidation, which is different from the method for preparing battery-grade nano-iron phosphate by air oxidation in Example 1, in which deionized water is added to the raw material liquid obtained in S2 to adjust the pH value to 2 in S3, and no gas is introduced to perform oxidation precipitation reaction under stirring and heating conditions, but after deionized water is added to the raw material liquid obtained in S2 to adjust the pH value to 2, excess H is added dropwise under stirring and heating conditions. 2 O2 (10% excess), react for 80 min, and the final solution pH is 1.0 to obtain a precursor slurry.

[0080] Comparative Analysis

[0081] The nano-iron phosphates prepared in Examples 1-3 and the nano-iron phosphates prepared in Comparative Examples 1 and 2 were tested and analyzed respectively, and the analysis results are shown in Table 1 below:

[0082] Table 1 Test analysis results

[0083] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Nano iron phosphate D50 particle size (μm) 1.43 2.82 2.69 10.87 4.83 Nano iron phosphate iron-phosphorus ratio 0.97 0.98 0.97 0.97 0.98

[0084] It can be seen from the data in Table 1 that the D50 particle size data and iron-phosphorus ratio of the nano-iron phosphate obtained in Examples 1-3 meet the technical requirements of the industry standard HG / T 4701-2021, while the D50 particle size data and iron-phosphorus ratio of the nano-iron phosphate obtained in Comparative Examples 1 and 2 do not meet the technical requirements of the industry standard HG / T 4701-2021. According to the comparison between Example 1 and Comparative Examples 1 and 2, it is feasible to regulate the particle size and morphology of iron phosphate by air oxidation and adding surfactants in the present invention. By adding surfactants, the formation of large particles can be suppressed in the iron phosphate grain growth stage, and then the uniform and stable growth of the grains can be controlled, while reducing particle agglomeration; using air instead of hydrogen peroxide significantly reduces the production cost, not only makes up for the problems of incomplete reaction and substandard iron-phosphorus ratio caused by the easy decomposition of hydrogen peroxide by heat, but also makes the reaction more sufficient, thereby eliminating the aging step and obtaining crystalline iron phosphate dihydrate in one step.

[0085] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A method for preparing battery-grade nano-iron phosphate by air oxidation, characterized in that: The following steps are involved: S1. dissolving iron powder in dilute phosphoric acid, stirring and heating the dilute phosphoric acid during the dissolution process, ultrasonically dispersing the dilute phosphoric acid, and filtering to obtain a filtrate; S2, adding a surfactant to the filtrate obtained in S1 to obtain a raw material solution; S3, adding deionized water to the raw material solution obtained in S2 to adjust the pH value to 1-2, and then introducing gas under stirring and heating conditions to perform an oxidation precipitation reaction to obtain a precursor slurry; S4. Post-process the precursor slurry obtained in S3 to obtain battery-grade nano iron phosphate.

2. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: The iron powder in S1 is pre-sieved with a 200-mesh sieve, and the iron powder is any one or a combination of ductile iron with an iron content of ≥97%, reduced iron powder with an iron content of ≥98%, and electrolytic iron powder with an iron content of ≥99%.

3. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: The molar ratio of iron powder to phosphoric acid in S1 is 1:2-4, the mass percentage concentration of dilute phosphoric acid is 15-40%, the dissolution temperature is 20-80°C, the dissolution time is 1-2h, the ultrasonic power of ultrasonic dispersion is 100-150w, and the ultrasonic frequency is 20-30kHz.

4. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: When a surfactant is added to S2, the filtrate is stirred and heated.

5. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 4, characterized in that: In S2, the filtrate is stirred and heated at a stirring speed of 400-600 rpm and a heating temperature of 50-80°C.

6. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: The surfactant in S2 is any one of citric acid, polyethylene glycol, hexadecyltrimethylammonium bromide and sodium hexadecylbenzenesulfonate.

7. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: The mass of the surfactant added to S2 is 1-5% of the theoretical amount of the precursor slurry produced in S3.

8. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: The flow rate of the gas introduced into S3 is 2.5-3.5 L / min, the temperature of the oxidation precipitation reaction is 80-100°C, the reaction time is 1-2h, and the stirring speed is 400-600rpm.

9. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: The gas introduced into S3 is any one of air, oxygen and ozone or a combination of several of them.

10. The method for preparing battery-grade nano-iron phosphate by air oxidation according to claim 1, characterized in that: The post-processing of the precursor slurry in S4 mainly includes: The precursor slurry obtained in S3 is filtered and washed, and calcined at a temperature of 450-550° C. for 4-6 hours to obtain nano iron phosphate.